2021
DOI: 10.22454/fammed.2021.500263
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Trauma-Informed Curricula for Primary Care Providers

Abstract: Background and Objectives: Traumatic experiences such as abuse, neglect, and household dysfunction have a lifetime prevalence of 62%-75% and can negatively impact health outcomes. However, many primary care providers (PCPs) are inadequately prepared to treat patients with trauma due to a lack of training. Our objective was to identify trauma-informed approach curricula for PCPs, review their effectiveness, and identify gaps. Methods: We systematically identified articles from Medline, Scopus, Web of Science, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…These cross-sectional results seemingly point to TIC training as a brief, organization-level strategy that not only can enhance the trauma-informed nature of health care provision but also is well-received by providers. Yet, the TIC training literature is in its nascence, and few longitudinal evaluations of TIC trainings for hospital-based health care providers exist 22,37. Ultimately, current findings call for follow-up studies that are methodologically robust and can measure change in trauma-informed practices in a systematic way.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…These cross-sectional results seemingly point to TIC training as a brief, organization-level strategy that not only can enhance the trauma-informed nature of health care provision but also is well-received by providers. Yet, the TIC training literature is in its nascence, and few longitudinal evaluations of TIC trainings for hospital-based health care providers exist 22,37. Ultimately, current findings call for follow-up studies that are methodologically robust and can measure change in trauma-informed practices in a systematic way.…”
Section: Discussionmentioning
confidence: 98%
“…Yet, the TIC training literature is in its nascence, and few longitudinal evaluations of TIC trainings for hospital-based health care providers exist. 22,37 Ultimately, current findings call for follow-up studies that are methodologically robust and can measure change in trauma-informed practices in a systematic way.…”
Section: Family and Community Healthmentioning
confidence: 97%
See 2 more Smart Citations
“…Trauma-informed principles in medical settings have been shown to improve patient satisfaction and the therapeutic care relationship. [23][24][25] Multiple studies have found that completion of TIC physical examination training was associated with positive outcomes for clinicians, such as increased awareness, confidence in abilities, and positive experiences. 13,[26][27][28] The future for TIC is to expand this perspective to an organization as a whole to be transformed into a trauma-responsive workplace.…”
Section: Future Directions For Ticmentioning
confidence: 99%